Real Legal Certainty and its Relevance Essays in honor of Jan Michiel Otto - Bedner, Adriaan; Oomen, Barbara (Law, Governance, and Development, 2018)
The concept of "real legal certainty" provides a much-needed corrective to the general attention legal certainty currently receives, emphasizing relations between citizens, adding socio-legal insight, and providing a "view from below" Real legal certainty thus leads to more realistic insights on how to build state institutions. The concept was introduced by Leiden University's professor of law and governance in developing countries Jan Michiel Otto, and can be considered a central pillar of his work. In this volume, friends and colleagues of Otto engage with the concept of real legal certainty against the backdrop of an ever-increasing interest in legal certainty in policy-making and academia, providing a wide variety of examples of its relevance. Drawing on case material from all over the world, they show how real legal certainty can be understood in a bottom-up manner and how it is relevant for building state institutions. They also show how the concept can gain in relevance by taking non-state actors into account. In all, the volume is important reading for all whom share Otto's interest in translating law in the books and into law in action.